High performance electromechanical actuators based on ionic liquid/poly(vinylidene fluoride). (December 2015) - Dias, J.C.; Lopes, A.C.; Magalhães, B.; Botelho, G.; Silva, M.M.; Esperança, J.M.S.S.; Lanceros-Mendez, S.
Abstract: Due to the increasing need of low voltage actuators, independent from electrochemical processes, electroactive actuators based on poly(vinylidene fluoride) composites with 10, 25 and 40% of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, [C2 mim] [NTf2 ], ionic liquid are prepared by solvent casting and melting. We show that the charge structure of [C2 mim] [NTf2 ] induces the complete piezoelectric β-phase crystallization of the PVDF within the composite and decreases its crystallinity fraction significantly. [C2 mim] [NTf2 ] also works as a plasticizer of PVDF, reducing the elastic modulus down to 12% of the initial value. Moreover, the composites show significant displacement and bending under applied voltages of 2, 5 and 10 Vpp. The displacement and bending of the composite membranes are also evaluated as a function of [C2 mim] [NTf2 ] content and sample thickness. Increasing amounts of ionic liquid result in larger deformations independently of the applied voltage.